WOMEN & SMES: EMPOWERING FOR BETTER ECONOMIC - Pancawati, Galuh; Ginting, Karnida Retta; Osnainillah, Juniar Andini (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
Covid has had an impact on reducing Indonesia's overall economic growth, data from BPS shows that at least the economy has fallen by -2.07 percent. This impact is felt by various existing economic sectors. However, there is an interesting phenomenon regarding how women improve their family's economic situation through various businesses starting from home businesses. New women entrepreneurs emerged during the pandemic. The role of women is increasingly influential in the transformation of the family's economic improvement and of course has an impact on the nation's economy in a broader context. Economic resilience is certainly one of the outcomes resulting from the emergence of women's small business activities. This paper examines the process of empowering women in women's SMEs during a pandemic seen from three stages, namely taking part, preparing, and protecting. This research is a qualitative descriptive study with a systematic literature review method by analyzing journals related to the title. The results show that various policies issued by the government have covered the first two stages, but protection has not yet been seen. Apart from the government, there is a significant role for community organizations and private companies including e-commerce to support women's MSMEs. Their role is to provide education and assistance to women entrepreneurs of SMEs. ABSTRAKSICovid berdampak pada penurunan pertumbuhan ekonomi Indonesia secara menyeluruh, data dari BPS menunjukkan setidaknya perekonomian turun sebesar -2,07 persen. Dampak ini dirasakan oleh berbagai sektor ekonomi yang ada. Namun demikian, terdapat fenomena yang menarik berkenaan dengan bagaimana perempuan memperbaiki keadaan ekonomi keluarga melalui berbagai usaha mulai dari usaha rumahan. Bermunculan wirausaha perempuan baru selama masa pandemi. Peran perempuan semakin berpengaruh dalam transformasi perbaikan perekonomian keluarga dan tentu berdampak pada perekonomian bangsa dalam konteks yang lebih luas. Ketahanan ekonomi tentu menjadi salah satu luaran yang dihasilkan dari bermunculannya kegiatan usaha kecil perempuan. Tulisan ini mengkaji bagaimana proses pemberdayaan perempuan dalam usaha umkm perempuan selama pandemi yang dilihat dari tiga tahapan, yaitu pemihakan, penyiapan, dan perlindungan. Penelitian ini adalah penelitian deskriptif kualitatif dengan metode systematic literature review dengan menganalisis jurnal-jurnal yang terkait dengan judul. Hasil menunjukkan berbagai kebijakan yang dikeluarkan pemerintah telah mencakup dua tahap awal, namun proteksi belum terlihat. Selain pemerintah, terdapat peran signifikan dari organisasi masyarakat dan perusahaan swasta termasuk e-commerce untuk mendukung UMKM perempuan. Mereka berperan memberikan edukasi dan pendampingan terhadap perempuan pengusaha UMKM.